The Only Canadians: Canada's French and the British Connection - Morrison, Katherine (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2008)
Canada has two long-standing national myths: Loyalism and the Conquest. The nature of these myths, their historical founding, and the tenacity with which they reinforce each other are examined. During Canada's early years, the name "Canadian" applied only to the nation's French. English Canadians were British. Working chronologically and using literary examples set in the context of their day, this essay demonstrates the resentment felt by French Canadians over Loyalism's grip on their English-speaking compatriots. Does Canada's continued adherence to the British monarchy keep Canada divided and prevent a sense of common nationality?